The Impact of Interactive Corporate Social Responsibility Communication on Corporate Reputation - Eberle, David; Berens, Guido A. J. M. 1974-; Li, Ting (2013)
Companies increasingly communicate about corporate social responsibility (CSR) through interactive online media. We examine whether using such media is beneficial to a company’s reputation. We conducted an online experiment to examine the impacts of interactivity in CSR messages on corporate reputation and word-of-mouth intentions. Our findings suggest that an increase in perceived interactivity leads to higher message credibility and stronger feelings of identification with the company, which also boost corporate reputation and word-of-mouth. This result implies that using interactive channels to communicate about CSR can improve corporate reputation. Our results also show that the detrimental impacts of negative user evaluations on corporate reputation are much higher than the favorable impacts of positive evaluations. This finding suggests that, despite the effectiveness of interactive communication channels, firms need to carefully monitor these channels.
Keywords: Social Media; Message credibility; Interactivity; Electronic word-of-mouth; Corporate Social Responsibility; Corporate Reputation